Thermal Stability of Antioxidant Compounds and Nutritional Profile of Functional Crackers Based on Surian Leaves - Anni Faridah; Ranggi Rahimul Insan; Sari Mustika; Risma Rahmatunisa; Munadia Insani; Efrina Efrina (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Kerupuk or cracker, a popular snack in Indonesia, is typically high in carbohydrates but low in functional components. Surian leaves (Toona sureni), which are rich in antioxidant compounds, have the potential to enhance the functional value of these crackers. However, the stability of these compounds during thermal processing remains largely unknown. This study aims to evaluate the effect of surian leaves addition and each processing stage (raw, boiling, drying, frying) on the proximate composition and antioxidant activity (IC50) of the crackers. This study utilized a factorial Completely Randomized Design (CRD) with two factors: the addition of surian leaves (0% and 16%) and four processing stages. The analyses included proximate composition and the DPPH antioxidant assay. The results showed that the addition of surian leaves significantly increased antioxidant activity (p < 0.001). The processing stages exerted a dominant influence on all parameters: boiling caused the leaching of water-soluble compounds; drying significantly increased protein and ash concentrations; while frying drastically elevated the fat content and was simultaneously the most detrimental stage for antioxidant activity. Despite the degradation, the surian leaves-fortified crackers consistently exhibited significantly higher antioxidant activity compared to the control at every processing stage. It can be concluded that surian leaves are an effective functional ingredient for crackers; however, the processing method is a critical determinant of the final product quality. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good health and well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible consumption and production